PENGARUH KEKAYAAN DAERAH (PAD), TOTAL ASET, JUMLAH PENDUDUK, TINGKAT KETERGANTUNGAN, DAN TEMUAN AUDIT TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi LKPD pada Provinsi Jawa Tengah Periode 2014-2016) - pankrasius traviatno suryadi (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to examine the influence of Regional Wealth (PAD), Total Assets, Total Population, Level of Dependency, and Audit Findings on the Level of Disclosure of Local Government Financial Statements (LKPD) in Central Java Province 2014-2016. The population in this study is all districts / cities across the province in Central Java in 2014-2016. The sample used is purposive sampling, so that obtained as much as 81 LKPD. The type of data used is secondary data. Data obtained from the official website of regencies/municipalities in Central Java Province in the form of financial statements that have been audited by BPK and BPS office of Central Java Representative. The analysis technique used is multiple linear regression method. The result of regression test shows that the regional wealth (PAD), Total Asset, Total Population, Level of Dependency, and Audit Finding simultaneously have a significant positive effect on the disclosure of Local Government Financial Statement. Partially, PAD and Dependency Level have no effect on LKPD disclosure, total assets have a significant positive effect on LKPD disclosure, total population and audit findings have significant negative effect on LKPD disclosure.